Sydney Memory and Ageing Study: An epidemiological cohort study of brain ageing and dementia. (December 2013) - Tsang, Ruby S. M.; Sachdev, Perminder S.; Reppermund, Simone; Kochan, Nicole A.; Kang, Kristan; Crawford, John; Wen, Wei; Draper, Brian; Trollor, Julian N.; Slavin, Melissa J.; Mather, Karen A.; Assareh, Arezoo; et al.
Abstract Non-demented community-dwelling older adults aged 70–90 years (n = 1, 037) randomly recruited from the electoral roll completed neuropsychological and medical assessments over six years. The overall prevalence of mild cognitive impairment (MCI) at baseline was 36.7%. Risk factors for MCI include APOE ϵ4 allele carrier status, high homocysteine, heart disease, poor odour identification, low visual acuity and low mental activity, but notable age and sex differences were observed. Neuropsychiatric symptoms were rare; depression was the most common and was associated with cognitive impairment in at least one domain as well as subsequent dementia 2 years later. Poorer cognitively demanding functional abilities were associated with cognitive impairment. Biomarkers for cognitive impairment and decline were identified. Inflammatory markers and plasma apolipoprotein levels were associated with poorer performance in the attention/processing speed domain. Measures of white matter lesions, white matter integrity, sulcal morphology and tractography were identified as novel biomarkers of early cognitive decline. Stronger deactivation in the posteromedial cortex with increasing memory load on functional MRI predicted future decline. Compared to previous reports, our prevalence rates of MCI were higher but rates of progression to dementia and reversion to normal were similar, as were risk factors for progression to dementia.